Numerical analysis of vanadium redox flow batteries considering electrode deformation under various flow fields - Xiong, Binyu; Li, Yang; Ding, Yuming; Wang, Jinsong; Wei, Zhongbao; Zhao, Jiyun; Ai, Xiaomeng; Fang, Jiakun (Journal of power sources, 2023)
The porous electrode of vanadium redox flow batteries (VRBs) is subject to deformation due to mechanical stress during stack assembling. The forces compress the electrode fiber into the flow channel and thus alter the electrode porosity ratio. Due to the complex mechanisms, the effects of resulting electrode morphological changes on VRB performance were usually ignored in existing studies. This paper proposes a three-dimensional VRB model considering the uneven electrode deformation to investigate the cell performance under different electrode compression ratios with three flow-field designs. Compression ratio (CR) and the intrusive part of the electrode are obtained under various mechanical stress by adjusting gasket thickness in the experiment. The proposed electrochemical model is established based on the comprehensive description of conservation laws and analyzed using the COMSOL platform. Three indices, namely the concentration overpotential, pressure drop, and distribution uniformity, are selected for the analysis under the three flow field designs and different CRs. The numerical study reveal that the pressure drop and the concentration overpotential are sensitive to the CR but less affected by the concentration uniformity. The minimum overpotential can be reached when the CR is around 40%–50%, depending on flow field designs, while a higher CR can cause a drastically increased pressure drop. It is also found that the interdigitated flow field with a CR of 45% is considered optimal. The insights from the proposed method demonstrate the significance of considering the effects of electrode deformation in the stack design under various flow fields. •A 3D electrochemical model considering unevenly electrodes deformation is proposed.•A non-uniform partitioning method for unevenly deformed electrodes is proposed.•The compression ratios under various mechanical stress are measured.•The interdigitated flow channels under CR of 45% demonstrate maximum performance.